Fiber Content and Antioxidant Activity of Chiapuding from Chia Seeds and Soybean Extract with Temple Flower Extract as a Dilution for Obesite Teenagers - Moulieda Rosyalia; Dera Elva Junita; Desti Ambar Wati; Alifiyanti Muharramah (Indonesian Journal of Health Research and Development, 2024)
The aim of this research was to analyze the fiber content and antioxidant activity in pudding made from chia seeds and soybean juice with butterfly pea flower extract. The type of research is experimental research, with the RAL (Completely Randomized Design) method, which is carried out by adding chia seeds to making pudding with 5 treatments, namely F0 (0%), F1 (2%), F2 (4%), F3 (6%) and F4 (8%). Fiber content analysis using the AOAC method and antioxidant activity analysis using the DPPH method were carried out at the Lampung State Polytechnic Laboratory. Data processing was carried out by ANOVA and Duncan tests using SPSS 20. The results of statistical tests on fiber content showed that there was no effect of adding chia seeds to making pudding with a p-value = 0.106 even though there was an increase in each formula. The highest fiber content in F4 (8%) is 5.86% or 5.8 gr/100 gr pudding, which can meet daily fiber needs, namely 2.7 -3.7 gr/day. The results of statistical tests on antioxidant activity show that there is an effect of adding chia seeds to make pudding with a p-value = 0.000. The highest IC50 antioxidant activity was in F4 (8%) at 6090 µg/mL, even though the IC50 value was in the weak category, the smaller the IC50 value, the stronger the antioxidant was in warding off free radicals. Based on research results, the more chia seed formula added, the higher the fiber content and the higher the IC50 antioxidant activity.